N + ion modified alpha-PbO porous electrode, preparation method thereof and application of N + ion modified alpha-PbO porous electrode in electro-catalytic synthesis of sodium borohydride
Through the N+ ion modified α-PbO porous electrode, the double layer structure on the cathode surface is changed, and the problem of B(OH)4-mass transfer is blocked in sodium borohydride synthesis is solved, and efficient sodium borohydride electrocatalytic synthesis is achieved. The current efficiency reaches 67.6%, and the method is environmentally friendly and energy-saving.
Patent Information
- Application Number
- CN202411216118.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-09-02
AI Technical Summary
In the prior art, the synthesis of sodium borohydride has a problem of low current efficiency, which is mainly due to the electrical double layer structure on the cathode surface that causes the mass transfer of B(OH)4- to be blocked, making it difficult to effectively reduce to BH4- at the cathode.
Through the combined process of ball milling-sintering-cationic active agent modification, an N+ ion modified α-PbO porous electrode is formed, which changes the double layer structure on the cathode surface, forms a positive charge layer, enhances the adsorption effect of the catalyst on -OH, and promotes B ( Mass transfer and conversion of OH)4- to BH4-.
The current efficiency of sodium borohydride has been significantly improved to reach 67.6%, and this method is relatively environmentally friendly and energy-saving, with good application prospects.
Smart Images

Figure CN119177467A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of green hydrogen production, in particular to N + An ion-modified α-PbO porous electrode, a preparation method thereof, and application in the electrocatalytic synthesis of sodium borohydride. Background Art
[0002] As a member of the hydrogen storage material family, sodium borohydride (NaBH4) has significant advantages such as high hydrogen storage density (10.8wt%), high purity of hydrogen produced, long-term stable storage and no pollution to the environment. Under ideal conditions, 1 mol of sodium borohydride can produce 4 mol of hydrogen, which makes the use of hydrogen energy very promising. However, after years of research, there are still many problems in the synthesis of sodium borohydride. The U.S. Department of Energy once made an unfeasible decision based on the high cost of recovering its hydrolysis byproduct sodium metaborate and the low efficiency of synthesizing sodium borohydride from sodium metaborate. At present, further exploration of solutions to these problems is still needed.
[0003] Although sodium borohydride has unparalleled advantages over other methods as a hydrogen source for fuel cells, if it is to be industrialized, it should meet the requirements of simple production process and low cost; and the byproduct sodium metaborate should also be recycled to avoid boron pollution. So far, the reported methods for recycling sodium borohydride after releasing hydrogen include: chemical reduction method, mechanical and chemical combination method and electrochemical method, but none of them has been industrialized. Theoretically, the first two methods require the introduction of reducing agents to achieve boron circulation, which is not only costly but also requires the treatment of byproducts introduced by the reducing agent; while the electrochemical method does not require the addition of reducing agents and achieves boron recycling through the electroreduction process.
[0004] The main problem in preparing sodium borohydride by electrochemical reduction is that during the electrolysis process, due to the repulsion of like charges and the attraction of opposite charges, B(OH)4 - Electromigration to the anode causes B(OH)4 near the cathode - The concentration decreases, resulting in B(OH)4 - Reduction to BH4 - It is very difficult, so the current efficiency of synthesizing sodium borohydride is extremely low. How to improve the double electric layer structure on the electrode surface and alleviate B(OH)4 - The repulsion at the cathode has always been a problem that has troubled many researchers. Therefore, in order to enable the efficient and low-cost large-scale synthesis of sodium borohydride, methods to effectively improve the double-layer structure on the cathode surface are of great research value. Summary of the invention
[0005] In view of the technical problems that the mass transfer of anions on the cathode surface is hindered and the reduction efficiency is low, the purpose of the present invention is to provide N +Ion-modified α-PbO porous electrode and its preparation method and application in electrocatalytic synthesis of sodium borohydride. The present invention combines α-PbO with a specific cationic surfactant through a ball milling-sintering-cationic active agent modification combined process to form a positive charge layer on the surface of the α-PbO catalyst, change the double electric layer structure on the cathode surface, and promote B(OH)4 - In the mass transfer process at the cathode, the modified α-PbO catalyst has an enhanced adsorption effect on -OH, and Pb-NO bonds are easily formed on the surface, which helps to activate the reactants on the catalyst surface and promote the conversion of the reactants to sodium borohydride.
[0006] The technical solution adopted by the present invention is as follows:
[0007] N + The preparation method of the ion-modified α-PbO porous electrode comprises the following steps:
[0008] 1) Put β-PbO powder and stainless steel balls into a ball mill, and grind them in a ball mill. The product after ball milling is micron flower-like α-PbO, which is then put into a N-containing cationic surfactant solution and stirred, and then filtered to obtain N + Ion-modified micro-flower-like α-PbO;
[0009] 2) N + Ion-modified micron flower-shaped α-PbO, sodium metaborate, conductive powder and paraffin are mixed and ground to form fine powder;
[0010] 3) Pressing the powder obtained in step 2) into an electrode sheet, using alumina as an embedding material, embedding the electrode sheet in alumina (alumina mainly plays a role of chemical protection to make the sample evenly heated), sintering in a muffle furnace, and finally taking out the electrode sheet after cooling in the furnace to obtain N + Ion-modified α-PbO porous electrode.
[0011] Furthermore, the particle size of the β-PbO powder in step 1) is in the range of 100-500 mesh, the diameter of the stainless steel ball is 10-20 mm, and the mass of the stainless steel ball is 4-8 times the mass of the β-PbO powder.
[0012] Furthermore, in step 1), the ball milling time is controlled at 40-80 hours, and the ball milling speed is 200-500 rpm. The ball milling speed determines the grain size of the sample powder. A long time can make the sample powder reach a certain mesh number, and the length of the ball milling time can control the uniformity of the powder grains.
[0013] Furthermore, the N-containing cationic surfactant is a mixture of one or more of dodecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, and sodium triacetoxyborohydride, preferably dodecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide or tetradecyltrimethylammonium bromide, and more preferably hexadecyltrimethylammonium bromide.
[0014] Furthermore, the concentration of the N-containing cationic surfactant solution is 5-50 g / L, preferably 10-30 g / L. The selection of the cationic surfactant is the key to whether it can be successfully loaded on the sample powder.
[0015] Furthermore, in step 1), the stirring time is 6-60 h, preferably 12-24 h.
[0016] Furthermore, in step 2), the sodium metaborate includes at least one of sodium metaborate tetrahydrate, sodium metaborate dihydrate or anhydrous sodium metaborate, and the particle size ranges from 300 to 700 meshes; the conductive powder includes a mixture of one or more of activated carbon, amorphous carbon, silver powder, carbon nanotubes, and conductive graphite powder.
[0017] Further, in step 2), the mass of sodium metaborate powder is N + The mass of the ion-modified micron flower-shaped α-PbO is 0.3-2.5 times, preferably 0.5-1 times; the conductive powder is N + The mass of the ion-modified micron flower-shaped α-PbO is 0.02-0.2 times, preferably 0.05-0.1 times; the paraffin is N + The concentration of ions is 0.02-0.2 times of that of the ion-modified micron flower-shaped α-PbO, preferably 0.05-0.1 times.
[0018] Furthermore, in step 3), the sintering temperature and the holding time are controlled at 100-300° C., preferably 200±20° C., and the holding time is controlled at 1-5 h, preferably 2-3 h.
[0019] The present invention also provides the N + The ion-modified α-PbO porous electrode is used as a cathode for electrocatalytic synthesis of sodium borohydride. The application method is: the cathode chamber and the anode chamber are separated by a cation exchange membrane, and the electrolyte in the anode chamber is 0.1-1 mol·L -1 Sodium hydroxide aqueous solution, the cathode electrolyte contains 0.1-1 mol·L -1 Sodium hydroxide and 0.05-0.5 mol·L -1 A mixed aqueous solution of sodium metaborate tetrahydrate, with the N + The ion-modified α-PbO porous electrode was used as the cathode and the graphite electrode as the anode. The current density of the electrolysis process was 5-20 mA cm -2, the electrolyte temperature is room temperature.
[0020] The present invention + Ion-modified α-PbO porous electrode for electroreduction of B(OH)4 - It has a good application in the field of catalysts. After ball milling, a large number of dislocations and oxygen vacancies are formed on the catalyst. These defects are B(OH)4 - It provides a large number of reaction sites. The modification of cations makes the catalyst surface positively charged, and anions migrate to N under the action of the electric field. + Modify the micron flower-shaped α-PbO porous electrode to obtain electrons to generate BH4 - , thus the reaction current efficiency is significantly improved.
[0021] The above scheme of the present invention has the following beneficial effects:
[0022] 1. The present invention uses a special surfactant (such as hexadecyltrimethylammonium bromide) to modify the α-PbO catalyst to form N + The ion-modified micron flower-like α-PbO forms a positive charge layer on the catalyst surface, which changes the double electric layer structure on the cathode surface and helps B(OH)4 - Mass transfer at the cathode.
[0023] 2. N prepared by the present invention + Ion-modified micron flower-shaped α-PbO porous electrode, ball milling process and special surfactant modification can increase the Zeta potential of the catalyst surface ( Figure 2 The adsorption of anions is enhanced.
[0024] 3. N prepared by the present invention + There are a large number of Pb-NO bonds on the surface of the ion-modified micro-flower-shaped α-PbO porous electrode, indicating that it is suitable for B(OH)4 - Medium (OH) - The adsorption and desorption effect is helpful for the activation and conversion of reactants on the electrode surface.
[0025] 4. N prepared by the present invention + Ion-modified micro-flower-shaped α-PbO porous electrode for electroreduction of B(OH)4 - It has significant advantages, and the current efficiency of synthesizing sodium borohydride reaches 67.6%. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a flow chart for preparing the α-PbO porous electrode in Example 1 of the present invention.
[0027] Figure 2Zeta potential diagrams of commercial β-PbO, ball-milled α-PbO, and electrodes treated with different surfactants.
[0028] Figure 3 N prepared in Example 1 of the present invention + Concentration and current efficiency of electrosynthesis of sodium borohydride on ion-modified micron flower-like α-PbO porous electrodes;
[0029] Figure 4 Concentration and current efficiency of the electrosynthesized sodium borohydride electrode prepared for commercially purchased β-PbO. DETAILED DESCRIPTION
[0030] The present invention will be further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0031] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0032] In the embodiment of the present invention, the embedding material is an alumina ball with a diameter of 1 mm. The current efficiency is calculated by the following formula:
[0033] Where η is the current efficiency, m is the actual current product mass, I is the electrolysis current, t is the electrolysis time, and k is the electrochemical equivalent. The electrochemical equivalent of synthesized sodium borohydride is 0.177 g / Ah.
[0034] Example 1
[0035] (1) 20 g of β-PbO powder was placed in a ball mill, and then 120 g of stainless steel balls were added to give a ball-to-powder ratio of 6:1. The sample was ground in a ball mill at 300 rpm for 60 h to obtain micron-flowered α-PbO. It was then placed in a cationic surfactant hexadecyltrimethylammonium bromide solution (0.5 g of cationic surfactant dissolved in 50 ml of water) and stirred for 24 h, and filtered to obtain N + Ion-modified micron flower-like α-PbO, denoted as CTAB-α-PbO.
[0036] (2) 12 g of N + Ion-modified micron flower-like α-PbO, 6 g of sodium metaborate tetrahydrate, 1 g of conductive graphite powder and 1 g of paraffin wax are continuously ground to form fine powder and mixed.
[0037] (3) The powder obtained in step (2) was pressed into an electrode sheet under a pressure of 70 MPa, and then buried under alumina balls (i.e., 1 mm alumina balls were used as embedding material, and the upper and lower surfaces of the electrode sheet were covered with alumina balls, which are the same in the following embodiments). The electrode sheet was sintered at 200° C. in a muffle furnace and maintained at this temperature for 2 h. After cooling in the furnace, the electrode sheet was taken out to obtain N + Ion modified micron flower-shaped α-PbO porous electrode. The specific process is as follows Figure 1 shown.
[0038] The N prepared in Example 1 + The ion-modified micron flower-shaped α-PbO porous electrode was used as the cathode and the graphite electrode was used as the anode. The electrolysis process was carried out in an electrolytic cell equipped with a cation exchange membrane. The CEM-II cation exchange membrane separated the cathode chamber from the anode chamber. The solution in the anode chamber was 0.5 mol·L -1 Sodium hydroxide solution, the solution in the cathode chamber is 0.5 mol·L -1 Sodium hydroxide and 0.2 mol·L -1 Sodium metaborate tetrahydrate mixed solution. The electrolysis process is at 10 mA cm -2 The electrolyte temperature was maintained at 25±1℃. The results of the changes in the sodium borohydride concentration and current efficiency produced by different electrolysis times are shown in Figure 3 The experimental results show that the current efficiency can reach up to 67.6% within 2 hours of electrolysis, and the concentration of sodium borohydride produced during 2 hours of electrolysis is as high as 8.1×10 -3 mol·L -1 .
[0039] The present invention combines α-PbO with a special cationic surfactant to form an electrode with unique catalytic function. + The ion-modified micron flower-shaped α-PbO porous electrode has excellent performance in the electrocatalytic reduction of sodium metaborate, can significantly improve the current efficiency, and makes the recovery of sodium metaborate more convenient. In addition, this method is more environmentally friendly and energy-saving, and has good application prospects.
[0040] Comparative Example 1
[0041] (1) 20 g of β-PbO powder was placed in a ball mill, and then 120 g of stainless steel balls were added. The sample was ground in a ball mill at 300 rpm for 60 h to obtain micron flower-like α-PbO, which was recorded as α-PbO. The only difference from step (1) of Example 1 was that the micron flower-like α-PbO was not stirred with the specific cationic surfactant hexadecyltrimethylammonium bromide.
[0042] (2) 12 g of micron flower-like α-PbO that has not been treated with hexadecyltrimethylammonium bromide, 6 g of sodium metaborate tetrahydrate, 1 g of conductive graphite powder and 1 g of paraffin are continuously ground into fine powder and mixed.
[0043] (3) The powder obtained in step (2) is compressed into an electrode sheet under a pressure of 70 MPa, and then buried under an alumina ball. It is sintered at 200°C in a muffle furnace and maintained at this temperature for 2 hours. After cooling in the furnace, the electrode sheet is taken out to obtain a micron flower-shaped α-PbO porous electrode.
[0044] The electrolysis experiment of Control Example 1 is the same as that of Example 1, except that the cathode is replaced by the micron flower-shaped α-PbO porous electrode of Control Example 1, and the other conditions remain unchanged. Finally, under the same current density and the same electrolysis time, the current efficiency within 2 h of electrolysis is up to 15%, and the sodium borohydride concentration generated after 2 h of electrolysis is 1.2×10 -3 mol L -1 .
[0045] Comparison of the experimental results of Example 1 of the present invention with those of Comparative Example 1 shows that the N + Ion-modified micro-flower-like α-PbO porous electrodes significantly improved the current efficiency.
[0046] Example 2
[0047] (1) 20 g of β-PbO powder was placed in a ball mill, and then 120 g of stainless steel balls were added. The sample was ground in a ball mill at 300 rpm for 60 h to obtain micron-flower-shaped α-PbO. Then it was placed in a cationic surfactant tetradecyltrimethylammonium bromide solution (0.5 g of cationic surfactant was dissolved in 50 ml of water) and stirred for 24 h. N + Ion-modified micron flower-like α-PbO, denoted as TTAB-α-PbO.
[0048] (2) 12 g of N + Ion-modified micron flower-like α-PbO, 6 g of sodium metaborate tetrahydrate, 1 g of conductive graphite powder and 1 g of paraffin wax are continuously ground to form fine powder and mixed.
[0049] (3) The powder obtained in step (2) is pressed into an electrode sheet at a pressure of 70 MPa, coated with an alumina ball, sintered in a muffle furnace at 200° C. and maintained at this temperature for 2 h. After cooling in the furnace, the electrode sheet is taken out to obtain a porous electrode.
[0050] The electrolysis experiment of Example 2 is the same as that of Example 1, except that the cathode is replaced by the porous electrode of Example 2, and the other conditions remain unchanged. Example 2 changes different types of N cationic surfactants, and the electrolysis results are: the current efficiency within 2 hours of electrolysis is up to 51%, and the concentration of sodium borohydride produced during 2 hours of electrolysis is 5.8×10 -3 mol·L -1 .
[0051] Example 3
[0052] (1) 20 g of β-PbO powder was placed in a ball mill, and then 120 g of stainless steel balls were added. The sample was ground in a ball mill at 300 rpm for 60 h to obtain micron-flowered α-PbO. Then it was placed in a cationic surfactant dodecyltrimethylammonium bromide solution (0.5 g of cationic surfactant was dissolved in 50 ml of water) and stirred for 24 h. N + Ion-modified micron flower-like α-PbO, denoted as DTAB-α-PbO.
[0053] (2) 12 g of micron flower-like α-PbO treated with dodecyltrimethylammonium bromide, 6 g of sodium metaborate tetrahydrate, 1 g of conductive graphite powder and 1 g of paraffin are continuously ground into fine powder and mixed.
[0054] (3) The powder obtained in step (2) is pressed into an electrode sheet at a pressure of 70 MPa, coated with an alumina ball, sintered in a muffle furnace at 200° C. and maintained at this temperature for 2 h. After cooling in the furnace, the electrode sheet is taken out to obtain a porous electrode.
[0055] The electrolysis experiment of Example 3 is the same as that of Example 1, except that the cathode is replaced by the porous electrode of Example 3, and the other conditions remain unchanged. Example 3 changes different types of N cationic surfactants, and the electrolysis results are: the current efficiency within 2 hours of electrolysis is up to 46%, and the concentration of sodium borohydride produced after 2 hours of electrolysis reaches 5.2×10 -3 mol·L -1 .
[0056] Example 4
[0057] (1) 20 g of β-PbO powder was placed in a ball mill, and then 120 g of stainless steel balls were added. The sample was ground in a ball mill at 300 rpm for 60 h to obtain micron-flowered α-PbO. Then it was placed in a cationic surfactant hexadecyltrimethylammonium bromide solution (0.5 g of cationic surfactant was dissolved in 50 ml of water) and stirred for 24 h. N + Ion-modified micro-flower-like α-PbO.
[0058] (2) 12 g of N + Ion-modified micron flower-like α-PbO, 6 g of sodium metaborate tetrahydrate, 1 g of conductive graphite powder and 1 g of paraffin wax are continuously ground to form fine powder and mixed.
[0059] (3) The powder obtained in step (2) is pressed into an electrode sheet under a pressure of 70 MPa, coated with an alumina ball, sintered in a muffle furnace at 300°C and maintained at this temperature for 4 hours. After cooling in the furnace, the electrode sheet is taken out to obtain a porous electrode.
[0060] The electrolysis experiment of Example 4 is the same as that of Example 1, except that the cathode is replaced by the porous electrode of Example 4, and the other conditions remain unchanged. Example 4 changes the control of calcination temperature and holding time, and conducts electrolysis experiments. The current efficiency within 2 hours of electrolysis is as high as 13.2%, and the concentration of sodium borohydride produced during 2 hours of electrolysis is as low as 1.0×10 -3 mol·L -1 .
[0061] Comparing the experimental results of Example 4 with those of Example 1, it can be seen that the control of calcination temperature and holding time also has a great influence on the electrocatalytic performance of the final porous electrode.
[0062] Example 5
[0063] (1) 20 g of β-PbO powder was placed in a ball mill, and then 120 g of stainless steel balls were added. The sample was ground in a Mitr ball mill at 300 rpm for 60 h to obtain micron-flowered α-PbO. Then it was placed in a cationic surfactant sodium triacetoxyborohydride solution (0.5 g of cationic surfactant was dissolved in 50 ml of water) and stirred for 24 h. N + Ion-modified micron flower-like α-PbO, denoted as STAB-α-PbO.
[0064] (2) 12 g of a catalyst treated with sodium triacetoxyborohydride, 6 g of sodium metaborate tetrahydrate, 1 g of conductive graphite powder and 1 g of paraffin wax are continuously ground into fine powder and mixed.
[0065] (3) The powder obtained in step (2) is pressed into an electrode sheet at a pressure of 70 MPa, coated with an alumina ball, sintered in a muffle furnace at 200° C. and maintained at this temperature for 2 h. After cooling in the furnace, the electrode sheet is taken out to obtain a porous electrode.
[0066] The electrolysis experiment of Example 5 is the same as that of Example 1, except that the cathode is replaced by the porous electrode of Example 5, and the other conditions remain unchanged. In Example 5, the N cationic surfactant is replaced by other types of cationic surfactants, and the electrolysis experiment is carried out. The current efficiency within 2 hours of electrolysis is as high as 18.6%, and the concentration of sodium borohydride produced during 2 hours of electrolysis is as low as 1.6×10 -3 mol·L -1 .
[0067] Example 6
[0068] (1) 20 g of commercial β-PbO powder was placed in a cationic surfactant hexadecyltrimethylammonium bromide solution (0.5 g of cationic surfactant was dissolved in 50 ml of water) and stirred for 24 h. N + Ion-modified β-PbO.
[0069] (2) 12 g of N + Ion-modified β-PbO, 6 g of sodium metaborate tetrahydrate, 1 g of conductive graphite powder and 1 g of paraffin wax are continuously ground to form fine powder and mixed.
[0070] (3) The powder obtained in step (2) is pressed into an electrode sheet at a pressure of 70 MPa, coated with an alumina ball, sintered in a muffle furnace at 200° C. and maintained at this temperature for 2 h. After cooling in the furnace, the electrode sheet is taken out to obtain a porous electrode.
[0071] The electrolysis experiment of Example 6 is the same as that of Example 1, except that the cathode is replaced by the porous electrode of Example 6, and the other conditions remain unchanged. In Example 6, the α-PbO obtained by ball milling is replaced by commercial β-PbO, and the electrolysis experiment is carried out. The results of the changes of the sodium borohydride concentration and the current efficiency produced by different electrolysis with the electrolysis time are shown in Figure 4 The experimental results show that the maximum current efficiency is 0.5% within 2 hours of electrolysis, and the concentration of sodium borohydride produced during 2 hours of electrolysis is as low as 0.1×10 - 3 mol·L -1 .
[0072] Through 6 examples and 1 control experiment, it can be clearly seen that the specific micron flower-shaped α-PbO is combined with the cationic surfactant hexadecyltrimethylammonium bromide to form N + Ion-modified micro-flower-like α-PbO can play a significant role in specific catalytic reduction reactions.
[0073] In addition, the Zeta potential diagram comparison results of commercial β-PbO, α-PbO obtained in Comparative Example 1, CTAB-α-PbO obtained in Example 1, TTAB-α-PbO obtained in Example 2, DTAB-α-PbO obtained in Example 3, and STAB-α-PbO obtained in Example 5 are shown in FIG. Figure 2 The N prepared by the present invention + Ion-modified micron flower-shaped α-PbO porous electrode, ball milling process and special surfactant modification can increase the Zeta potential of the catalyst surface ( Figure 2 The biggest obstacle to the reduction of metaborate anions at the cathode is the repulsion of the same charge, which makes the reaction difficult; however, the Zeta potential of the catalyst surface after the modification of the present invention increases, the adsorption of anions is enhanced, the activation and conversion of the reactants on the electrode surface are promoted, and the electrocatalytic activity is greatly improved.
[0074] The contents described in this specification are merely an enumeration of implementation forms of the inventive concept, and the protection scope of the present invention should not be regarded as being limited to the specific forms described in the embodiments.
Claims
1. N + The method for preparing an ion-modified α-PbO porous electrode is characterized in that The following steps are involved: 1) Put β-PbO powder and stainless steel balls into a ball mill and mill them in a ball mill. The product after ball milling is micron flower-like α-PbO, which is then put into a N-containing cationic surfactant solution and stirred. Then, N + Ion-modified micro-flower-like α-PbO; 2) N + Ion-modified micron flower-shaped α-PbO, sodium metaborate, conductive powder and paraffin are mixed and ground to form fine powder; 3) The powder obtained in step 2) is pressed into an electrode sheet, and alumina is used as an embedding material. The electrode sheet is embedded in alumina and sintered in a muffle furnace. Finally, the electrode sheet is taken out after cooling in the furnace to obtain N + Ion-modified α-PbO porous electrode.
2. The N according to claim 1 + The method for preparing an ion-modified α-PbO porous electrode is characterized in that The particle size of the β-PbO powder in step 1) is in the range of 100-500 mesh, the diameter of the stainless steel ball is 10-20 mm, and the mass of the stainless steel ball is 4-8 times the mass of the β-PbO powder.
3. The N according to claim 1 + The method for preparing an ion-modified α-PbO porous electrode is characterized in that In step 1), the ball milling time is controlled at 40-80 h, and the ball milling rate is controlled at 200-500 rpm.
4. The N according to claim 1 + The method for preparing an ion-modified α-PbO porous electrode is characterized in that In step 1), the N-containing cationic surfactant is a mixture of one or more of dodecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, and sodium triacetoxyborohydride, preferably dodecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide or tetradecyltrimethylammonium bromide, and the concentration of the solution is 5-50 g / L, preferably 10-30 g / L; the stirring time in step 1) is 6-60 h, preferably 12-24 h.
5. The N according to claim 1 + The method for preparing an ion-modified α-PbO porous electrode is characterized in that In step 2), the sodium metaborate includes at least one of sodium metaborate tetrahydrate, sodium metaborate dihydrate or anhydrous sodium metaborate, and the particle size ranges from 300 to 700 meshes; the conductive powder includes a mixture of one or more of activated carbon, amorphous carbon, silver powder, carbon nanotubes, and conductive graphite powder.
6. The N according to claim 1 + The method for preparing an ion-modified α-PbO porous electrode is characterized in that In step 2), the mass of sodium metaborate powder is N + The conductive powder is 0.3-2.5 times the mass of ion-modified micron flower-shaped α-PbO, preferably 0.5-1 times; + The mass of the ion-modified micron flower-shaped α-PbO is 0.02-0.2 times, preferably 0.05-0.1 times; the paraffin is N + The ion-modified micron flower-shaped α-PbO is 0.02-0.2 times, preferably 0.05-0.1 times.
7. The N according to claim 1 + The method for preparing an ion-modified α-PbO porous electrode is characterized in that In step 3), the sintering temperature and the holding time are controlled at 100-300°C, preferably 200±20°C, and the holding time is controlled at 1-5 h, preferably 2-3 h.
8. N prepared by the method of any one of claims 1 to 7 + Ion-modified α-PbO porous electrode.
9. The N according to claim 8 + Application of ion-modified α-PbO porous electrode as cathode for electrocatalytic synthesis of sodium borohydride.
10. The use according to claim 9, characterized in that The cathode chamber and the anode chamber are separated by a cation exchange membrane, and the electrolyte in the anode chamber is 0.1-1 mol·L -1 Sodium hydroxide aqueous solution, the cathode electrolyte contains 0.1-1 mol·L -1 Sodium hydroxide and 0.05-0.5 mol·L -1 A mixed aqueous solution of sodium metaborate tetrahydrate, with the N + The ion-modified α-PbO porous electrode was used as the cathode and the graphite electrode as the anode. The current density of the electrolysis process was 5-20 mA cm -2 , the electrolyte temperature is room temperature.
Citation Information
Patent Citations
Solid-phase catalytic electrode with shell sleeve structure, preparation method of solid-phase catalytic electrode and application of solid-phase catalytic electrode in electro-synthesis of sodium borohydride
CN116536701A
Apparatus for preparing boron hydride by electrolysis
CN1584122A
Preparation method of lead dioxide porous electrode
CN1924102A
Method and apparatus for manufacturing boron hydride compound
JP2003247088A
